Youth and social support: a look at the social networks of students from Pará (Práxis Educativa, 2019)
This study investigated the social networks of students from Pará, Brazil, through their functional aspect, which in a systemic perspective corresponds to the person-context-time interactions that may influence the various biopsychosocial aspects. Therefore, the social network is associated with the close and significant relationships established between the individual and the environment and should be perceived as a protective factor, satisfying their needs and desires, as they will allow them, in adverse situations, to request this assistance, balancing the relationships between risk and protective factors. 643 students from public schools participated in the research, aged 13 to 24 years old (m=16.56; sd=2.37), of both sexes. The Brazilian Youth Questionnaire was applied and, for this study, the questions regarding the perceptions of family, school and community support were used, as well as the question of personal protection factors. The results indicated that social networks act as a social support network, highlighting the emotional support perceived in all social networks. Significant correlations (p> 0.005) were observed between the perception of support in school, family, self-esteem and self-efficacy variables. The results highlighted the importance of social networks for the construction and maintenance of personal protection factors that can assist in the process of engagement, mobilization and social transformation.Keywords: Youth. Social Network. Social Support.